2015
DOI: 10.1021/acs.jpcb.5b00344
|View full text |Cite
|
Sign up to set email alerts
|

Conductive and Biphasic Pulses in Tunable Resistive Pulse Sensing

Abstract: This experimental study concerns the occurrence of biphasic pulses generated during tunable resistive pulse sensing (TRPS) of 200 nm carboxylate polystyrene spheres. In TRPS, a short-lived pulse in ionic current is observed when an individual colloid passes through a pore which separates two fluid reservoirs. The pulse is conventionally resistive, but conductive pulses are observed under certain experimental conditions, as well as biphasic pulses which include both resistive and conductive components. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 44 publications
5
62
0
Order By: Relevance
“…The observation of rectification behaviour does illustrate that the enriched ion zone at the pore mouth used to describe the rectification properties of smaller pores 24,42 sufficiently exerts an influence across the larger opening, even when the electrical DL is much shorter than the opening D s . This effect has also been attributed to biphasic pulse behaviour in TRPS 49 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 75%
See 2 more Smart Citations
“…The observation of rectification behaviour does illustrate that the enriched ion zone at the pore mouth used to describe the rectification properties of smaller pores 24,42 sufficiently exerts an influence across the larger opening, even when the electrical DL is much shorter than the opening D s . This effect has also been attributed to biphasic pulse behaviour in TRPS 49 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 75%
“…This effect is seen to a greater extent within conical pores, and typically recorded for pore openings where the diameter, D s , is equivalent to the electrical double layer, DL, thickness, 24,48 although the DL does not need to fully extend across the pore opening 24 , and larger pores exhibit current rectification effects 23,49 .…”
Section: Assay 1 -Measuring Translocation Times From Resistive Pulsesmentioning
confidence: 85%
See 1 more Smart Citation
“…High aspect ratio nanopores are available to researchers with a product called qNano. [73][74][75][76][77] This measurement system dynamically adjusts the diameter of the through-hole made in the polymer. With high aspect ratio nanopores, the particle diameter and zeta potential of the analyte are obtained by utilizing the fact that Ip and td have information on the volume, particle velocity, and surface charge of the analyte.…”
Section: •2 Flow Dynamics Of High Aspect Ratio Nanoporesmentioning
confidence: 99%
“…Studies have shown that ionic strength, off-axial translocation, the pore wall charge density and applied potential can affect the pulse size and width. [29][30][31][32] In cases where the charge double layers around the particles and pore walls interact, conductive pulses and ion current rectification can also be observed. 21,33,34 To help understand how the charge density effects the sensitivity of Aptamer RPS assays here we choose two known aptamers to heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%